Improving NASICON Sinterability through Crystallization under High-Frequency Electrical Fields - Lisenker, Ilya; Stoldt, Conrad R. (Frontiers in Energy Research, 2016)
The effect of high-frequency (HF) electric fields on the crystallization and sintering rates of a lithium aluminum germanium phosphate (LAGP) ion conducting ceramic was investigated. LAGP with the nominal composition Li1.5Al0.5Ge1.5(PO4)3 was crystallized and sintered, both conventionally and under effect of electrical field. Electrical field application, of 300 V/cm at 1 MHz, produced up to a 40% improvement in sintering rate of LAGP that was crystallized and sintered under the HF field. Heat sink effect of the electrodes appears to arrest thermal runaway and subsequent flash behavior. Sintered pellets were characterized using X-ray diffraction, scanning electron microscope, TEM, and electrochemical impedance spectroscopy to compare conventionally and field-sintered processes. The as-sintered structure appears largely unaffected by the field as the sintering curves tend to converge beyond initial stages of sintering. Differences in densities and microstructure after 1 h of sintering were minor with measured sintering strains of 31 vs. 26% with and without field, respectively. Ionic conductivity of the sintered pellets was evaluated, and no deterioration due to the use of HF field was noted, though capacitance of grain boundaries due to secondary phases was significantly increased.